Early detection of prostate cancer in firefighters: a register-based study of prognostic factors and survival. Issue 3 (11th September 2021) - Jakobsen, Jarle; Veierød, Marit B; Grimsrud, Tom K; Fosså, Sophie Dorothea; Hammarström, Bato; Kjærheim, Kristina
Abstract : Objectives: To examine age at diagnosis, prognostic factors and survival of prostate cancer (PCa) in Norwegian firefighters and three other occupations undergoing occupational health check-ups, and comparing with PCa cases in the general population. Methods: All PCa cases diagnosed in 1960–2017 were extracted from the Cancer Registry of Norway. Firefighters, military employees, pilots and police officers were identified through occupational data from Statistics Norway. Age at diagnosis, clinical stage, prostate-specific antigen (PSA), Gleason score, performance status and overall survival and PCa-specific survival in cases in these occupations were compared with cases in the general population. Results: Firefighters were significantly younger at PCa diagnosis than cases in the general population in 1960–1993 (mean difference: 2.1 years) and 2007–2017 (mean difference: 4.3 years). At diagnosis, firefighters had significantly lower PSA values, Gleason scores and performance status scores than the general population. Firefighters diagnosed in 2007–2017 had lower risk of all-cause death than the general population (crude HR 0.71 (0.53–0.95)). No difference remained after adjusting for age at diagnosis (HR 1.03 (0.77–1.37)). Firefighters were older at diagnosis in 1994–2006 (mean difference: 3.0 years), but showed no other significant differences in age at diagnosis, PSA values, Gleason scores or performance status compared with military employees, pilots and police officers. Conclusions: Younger age and better prognostic factors at PCa diagnosis among firefighters and other occupations with requirements for health check-ups than cases in the general population may indicate an increased diagnostic intensity, likely contributing to elevated PCa incidence in such occupations.